A Typology of Linguistic Field Research - Omar, Asmah Haji (Journal of Modern Languages, 2017)
This study attempts to give a written form of the language/dialect to its own speakers and to have documentation on the language dialect as a step to placing it in the inventory of the world’s languages. According to the mentioned purposes in the study, the linguist in upstream research has 10 set his/her objectives, which can be summarised into descriptions of the systems and structures of the phonology, morphology, syntax and semantics of the language/dialect concerned. The study also typifies the various types of research which require the researcher to get first-hand information from the source (s).